Impact of water quality on Chronic Kidney Disease of unknown etiology (CKDu) in Thunukkai Division in Mullaitivu District, Sri Lanka - Kalaivani, G.; Prabagar, S.; Uthpala Apekshani, J.; Gobalarajah, R.; Sittampalam, R.; Prabagar, J. (BMC Nephrology, 2020)
Background: Increase in the number of cases in Chronic Kidney Disease of Unknown etiology (CKDu) in Sri Lanka has become a health issue of national concern. Even though, Northern Province is not identified as a high-risk province, there is an increasing trend of CKDu after the end of civil war in the Northern Province. Methods: The present study was conducted in Thunukkai Division in Mullaitivu District to investigate the socio demographic and clinical pattern of CKDu patients and to evaluate the quality of their water sources. The samples were selected by using stratified purposive random sampling method which represented 29% of total CKDu patients in Thunukkai Division. Pretested structured questionnaire was administered to collect the data from the CKDu patients. The association between serum creatinine excreted by CKDu patients and the water quality parameters were determined by using linear regression model. Results: Among the patients, 80% were male with over 68% falling in the age range of 50–70. Majority (90%) were involved in agriculture related occupation. Smoking and alcohol consumption were detected as common habits among 40% of the patients. Secondarily developed, hypertension (60%) and diabetes (34%) were reported as common diseases in the area. Dug wells served as the commonest source of drinking water in the area (90% households) together with few tube wells. Physicochemistry of more than 50% of the water samples revealed higher electric conductivity, salinity, total dissolved solids, total hardness and Na levels compared to drinking water standards in Sri Lanka. Conclusions: Serum creatinine levels of the CKDu patients were significantly and negatively correlated with phosphate while positively correlated with total dissolved solids (TDS) and arsenic content of the drinking water. Geospatial mapping of TDS and arsenic in drinking water with the occurrence of higher serum creatinine levels confirmed the same trend. Thus, the total dissolved solids and arsenic in drinking water may have positive correlation with the occurrence of CKDu in Thunukkai region in the Mullaitivu District of Sri Lanka.
Keywords: Chronic kidney disease of unknown etiology; Water quality parameters; Serum creatinine